2005
DOI: 10.1007/s10631-005-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Colloidal Structures in Soils of Various Zonalities

Abstract: It has been demonstrated [1][2][3][4][5] that soil solutions are structured colloids and that they affect many properties of soils. Attempts to isolate a soil solution in order to study it using electron microscopy were inefficient [6]. Therefore, the need appeared for techniques to observe colloidal structures directly in soils rather than separate fragments of colloidal structures isolated from the soil and, thus, exposed to external factors.Small-angle neutron and X-ray scattering may be classified as such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The absence of a deviation of the dΣ(q)/dΩ curve from the power law (the onset of the Guinier regime) at small values of q means that the upper self-similarity limit ξ of the surface fractal is larger than the maximum size R max of the inhomogeneities (pores) that can be detected in the experiment with a given resolution: R max = 3.5/q min ≈ 60 nm. Thus, the observed scattering patterns are typical for scattering from system possessing a disordered porous (solid phase-pore medium) structure with fractal phase boundaries [83][84][85] including natural systems represented by rock fragments from shallow soils [86] and soil aggregates from mature soils [87].…”
Section: Mesostructure and Fractal Properties Of Moraine Samplesmentioning
confidence: 99%
“…The absence of a deviation of the dΣ(q)/dΩ curve from the power law (the onset of the Guinier regime) at small values of q means that the upper self-similarity limit ξ of the surface fractal is larger than the maximum size R max of the inhomogeneities (pores) that can be detected in the experiment with a given resolution: R max = 3.5/q min ≈ 60 nm. Thus, the observed scattering patterns are typical for scattering from system possessing a disordered porous (solid phase-pore medium) structure with fractal phase boundaries [83][84][85] including natural systems represented by rock fragments from shallow soils [86] and soil aggregates from mature soils [87].…”
Section: Mesostructure and Fractal Properties Of Moraine Samplesmentioning
confidence: 99%
“…Insight about the structural organization of pri mary HS formations into larger objects (we shell denote them as clusters 4 several tens to several hun dreds of nanometers in size can be obtained by com paring the data on the study of HS solutions [57,62,63] and soils [35][36][37] by the SANS method. The frac tal organization of HS clusters in solutions and the soil colloidal component was noted in both cases.…”
Section: Structure Of Soil Gelsmentioning
confidence: 99%
“…The frac tal organization of HS clusters in solutions and the soil colloidal component was noted in both cases. In the soils, the fractal organization of the soil gels [35][36][37] was attributed to the specific arrangement of the humic gel of inorganic particles in the homogeneous matrix. However, some data contradicted this inter pretation of the SANS study of soils.…”
Section: Structure Of Soil Gelsmentioning
confidence: 99%
“…Studying humic acid solutions, Osterberg showed using the small-angle neutron scattering method that primary humic acid particles with a size of 2-10 nm form fractal clusters with a size of 100-200 nm in solutions (1). Fedotov found that in soils, as well as in solutions of humic acids, there are also primary particles of humic substances of 2-10 nm in size, forming fractal clusters of 100-200 nm in size (2), which in turn, together with mineral particles, form soil gels.…”
mentioning
confidence: 99%